RETRACTED: Greening SMEs: Breaking barriers and building futures - Subhani Muhammad Imtiaz; Dyussembekova Zhanar; Ezhak Evgenia; Osman Amber (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001